Effect of acidic electrolysed water and pulsed light technology on the sensory, morphology, and bioactive compounds of Pennywort (Centella asiatica L.) leaves - Rosli, Siti-Zaharah; Mohd Adzahan, Noranizan; Karim, Roselina; Mahmud Ab Rashid, Nor-Khaizura (Multidisciplinary Digital Publishing Institute, 2022)
Pennywort (Centella asiatica) is a herbaceous vegetable that is usually served in the form of fresh-cut vegetables and consumed raw. Fresh-cut vegetables are in high demand as they offer convenience, have fresh-like quality and are potentially great for therapeutic applications. However, it could be the cause of foodborne outbreaks. Pulsed light is known as a decontamination method for minimally processed products. The aim of this study was to determine the influence of pulsed light in combination with acidic electrolysed water on the sensory, morphological changes and bioactive components in the leaves of pennywort during storage. A combination of soaking with acidic electrolysed water (AEW) at pH 2.5 and pulsed light (PL) treatment (1.5 J/cm2) was tested on the leaves of pennywort. After treatment, these leaves were refrigerated (4 ± 1 °C) for two weeks and evaluated on the basis of sensory acceptance, the visual appearance of the epidermal cell and bioactive compounds. In terms of sensorial properties, samples treated with the combined treatment were preferred over untreated samples. The combination of AEW and PL 1.5 J/cm2 was the most preferred in terms of purchasing and consumption criteria. Observations of the epidermal cells illustrated that PL treatment kept the cell structure intact. The bioactive phytocompounds found in the leaves of pennywort are mainly from the triterpene glycosides (asiaticoside, madecassoside, asiatic acid and madecassic acid) and are efficiently preserved by the combined treatment applied. In conclusion, the combination of acidic electrolysed water and pulsed light treatment is beneficial in retaining the sensory quality and bioactive compounds in the leaves of Pennywort during storage at 4 ± 1 °C.